Propensity-matched comparison of the long-term outcome of the Nunn and two-patch techniques for the repair of complete atrioventricular septal defects. (21st April 2019) - Bell, Douglas; Thakeria, Priyanka; Betts, Kim; Justo, Robert; Jalali, Homayoun; Wijesekera, Vishva; Venugopal, Prem; Karl, Tom; Alphonso, Nelson
Abstract: OBJECTIVES: To compare the long-term performance of the Nunn and 2-patch techniques for the repair of complete atrioventricular septal defects. METHODS: Between January 1995 and December 2015, a total of 188 patients (Nunn n  = 41; 2-patch n  = 147) were identified from hospital databases. Univariable Cox regression was performed to calculate the risk of reintervention in each group. Propensity score matching was used to balance the Nunn group and the 2-patch group. RESULTS: Baseline characteristics including age at surgery, weight, trisomy 21, other cardiac anomalies, previous operations and preoperative atrioventricular valve regurgitation did not differ between the 2 groups. Overall, there was no difference in mortality between the 2 groups ( P  = 0.43). Duration of cardiopulmonary bypass (CPB) and myocardial ischaemia time were 29 min ( P  <   0.001) and 28 min ( P  <   0.001) longer, respectively, in the 2-patch group. Median follow-up was 10.8 years (2–21 years). Unadjusted Cox regression did not reveal a significant difference in the risk of reoperation for either group 9 years after initial surgery [hazard ratio (HR) (Nunn) 0.512, 95% confidence interval 0.176–1.49; Nunn 89%; 2-patch 82%]. This finding was reiterated from Cox regression performed on the propensity-matched sample (31 pairs). The probability of freedom from moderate or worse left atrioventricular valve regurgitation or left ventricular outflow obstruction was similar in the 2 groups. CONCLUSIONS: The Nunn and 2-patch techniques are comparable in terms of the long-term mortality and probability of freedom from reoperation, moderate or severe left atrioventricular valve regurgitation and left ventricular outflow obstruction. However, the duration of CPB and myocardial ischaemia is longer in the 2-patch group.